Identity and parentage of some South American grapevine cultivars present in Argentina - Aliquo, Gustavo; Torres, Maria Del Rocio; Lacombe, Thierry; Boursiquot, Jean-Michel; Laucou, Valerie; Gualpa, Jose Luis; Fanzone, Martín Leandro; Sari, Santiago Eduardo; Perez Peña, Jorge Esteban; Prieto, Jorge Alejandro (2017)
Background and Aims: Based on 19 nuclear simple sequence repeat markers and parental analysis, we aimed to identify and propose the pedigree of different accessions held at the Estación Experimental Agropecuaria Mendoza of the Instituto Nacional de Tecnología Agropecuaria germplasm collection. The results were compared with data recorded in large, international databases. Methods and Results: We identified 37 different cultivars, of which 18 were original and not previously identified. The parentage analysis showed that European cultivars, such as Muscat of Alexandria, Muscat à Petits Grains, Listán Prieto, Mollar Cano and Malbec, were involved in natural crossings resulting in different South American cultivars. Conclusions: Many of the cultivars identified here represent unique individuals based on their genotype. The number of cultivars that participated as progenitors in the origin of South American germplasm is higher than previously thought. Significance of the Study: Germplasm collections planted many years ago play a key role in the conservation and characterisation of genotypes that otherwise may have been lost. It is highly probable that there might be other genotypes not identified and mixed in old vineyards. The identification, rescue and conservation of these genotypes are a challenge to preserve the existing genetic variability.